مغرب اور اسلام : باہمی تعارف و تخالف کی مختصر تاریخ (Al Basirah, 2020)
Islam and the West is a common term generally used for the two differentand notable civilizations of the World. Most of the people are actually notaware of the real connotation and perspective of this term and of mutualinteraction and encounter of the two. This paper studies the historicalcontact of Islam and the west and gives a comprehensive account on thesubject. It finds that the interaction of Islam and the West was and has beeninimical and uncongenial. The real cause of this hostility is the irrefutableand indefensible historical prejudices of the West against Islam andMuslims. To perish this mutual repugnance west will have to bring itselfout from this bias. However some of the present day Muslims, who havetaken on aggressive approaches and attitudes towards the west, also have tobring themselves out from their unislamic lookouts and acts.
Keywords: Islam and the West, historical interface, uncongenial, historical prejudices of the West.